Analysis of the Integration of SDGs Values in Learning Science Project in Vocational Schools to Build a Sustainable Lifestyle - Syaipul Hayat, Muhammad; Yunus, Muhammad; Qotrun Nada, Noora; Suma, Sumarno (KnE Social Sciences, 2024)
Vocational High School (VHS) students carry out a significant number of project activities as outputs of learning science projects, necessitating the use of large quantities of materials. In addition, the sustainability of the project products has not been thoroughly considered, as the focus often stops at the title of the work. This article aims to analyze the application of SDGs (Sustainable Development Goals) values in learning science projects in VHS to build a sustainable lifestyle. The study utilized a quantitative descriptive approach, examining the results of questionnaires filled out by respondents who are vocational teachers in Central Java. The results showed that, on average, each school had not applied SDGs values in learning science projects. Some carry out the principles of SDGs such as orienting to economic or environmental aspects, but they do not fully understand the essence of these values. These indicators are integral to the SDGs, and their application has not been optimal. In addition, in the application of science project learning, the determination of project themes and materials is still oriented towards product creation. Therefore, students have not been encouraged to align their thoughts with building a sustainable lifestyle. Thus, there needs to be an effective learning strategy to integrate SDGs values in learning science projects in VHS so that projects are oriented towards product production alone and pay attention to sustainability values. Keywords: SDGs (Sustainable Development Goals), IPAS project, sustainable lifestyle,